Betaine Alleviates High-Fat Diet Induced Excessive Lipid Deposition in Gibel Carp Hepatopancreas and L8824 Cells by Enhancing VLDL Secretion through HNF4α/MTTP Pathway - Xiaojing Dong; Jianqiao Wang; Mengjie Zhao; Xuedi Du; Hongying Fan; Yuanyuan Fu; Zhiyuan Gong; Shuyan Miao (Aquaculture Nutrition)
Betaine, a methyl donor, plays a crucial role in lipid metabolism. Previous studies have shown that appropriate betaine supplementation in a high-fat diet reduces triglycerides (TG) of serum and hepatopancreas in fish. However, the underlying mechanism remains unclear. This study examined whether betaine can enhance the secretion of very low-density lipoprotein (VLDL) and sought to identify the specific mechanisms through which this enhancement occurs. A lipid accumulation model was established in gibel carp and L8824 cells using a high-fat diet and oleic acid, respectively. Different doses of betaine (1, 4, and 16 g/kg in the diet; 400 μmol in cell culture) were administered, and measurements were taken for lipid deposition, gene expression of HNF4α, MTTP, and ApoB, as well as the regulation of Mttp and Apob promoters by HNF4α. The results showed that betaine supplementation mitigated lipid droplet accumulation, TG levels, and VLDL production induced by the high-fat diet in gibel carp hepatopancreas and L8824 cells. Moreover, betaine not only increased VLDL content in the cell culture supernatant but also reversed the inhibitory effects of the high-fat diet on protein expression of MTTP, ApoB, and HNF4α in both gibel carp hepatopancreas and L8824 cells. Additionally, HNF4α exhibits transactivating activity on the promoter of Mttp in gibel carp. These findings suggest that betaine supplementation exerts its effects through the HNF4α/MTTP/ApoB pathway, promoting the assembly and secretion of VLDL and effectively reducing lipid accumulation in the hepatopancreas of farmed gibel carp fed a high-fat diet.